Impacts of cadmium on the growth, yield and mineral nutrition of boro rice (BRRI dhan28): Impacts of Cd on rice - Islam, Md Mahmudul; Mohiuddin, A.S.M (Dhaka University Journal of Biological Sciences, 2026)
Cadmium (Cd) is a nonessential trace element in plants that is ubiquitous in the environment. Random disposal of urban and industrial refuses such as dyeing, spinning, tanning, smelting, mining, metal manufacturing, and application of synthetic phosphate fertilizers in cropping lands enhance the concentration of Cd in the soils, crops and its ultimate goal in the food chain which are carcinogenic to human health. A pot experiment has been undertaken to evaluate the effect of cadmium on the growth, yield, mineral nutrition and transfer of cadmium in the Boro rice (BRRI dhan28) crops. Boro rice was grown in untreated (control) and 03, 05, 07, 09, 15, 30, 60 and 90 mg/kg Cd as 3CdSO4, 8H2O treated soils. A significant reduction of fresh weight, dry weight and grain yield of BRRI dhan28 was initiated at 3mg/kg soil and with increasing successive application of cadmium; growth and yield of BRRI dhan28 rice plants reduced significantly. Similarly, with the increasing rate of cadmium application, a significant reduction of N, P, K, Ca and Mg was recorded from 3mg/kg to upwards. On the other hand, cadmium concentration in grains, straw and roots of rice increased with increased cadmium levels in soils. Cadmium concentration in the grains, straw and roots followed the order: Roots > Shoots > Grains and 3mg/kg soil was considered as threshold of cadmium toxicity of BRRI dhan28 rice variety. Plant died at 60 and 90 mg/kg doses of cadmium. Dhaka Univ. J. Biol. Sci. 35(1): 151-164, 2026 (January)